Faktor Yang Berpengaruh Terhadap Kesehatan Mental Perawat Di Ruang Rawat Inap Jiwa RSKD Dadi Kota Makassar - Difa Amru Azzahra Mawardi; Nurmiati Muchlis; Alfina Baharuddin (Pusat Kajian dan Pengelolaan Jurnal FKM UMI, 2026)
RSKD Dadi Makassar City is one of the referral hospitals in South Sulawesi that handles a large number of patients with mental disorders. This results in the hospital having a fairly high workload, especially in the psychiatric inpatient unit. Based on initial observations and interviews, it was found that during one night shift, only two nurses had to handle up to 60 patients. This condition clearly illustrates the imbalance between the number of medical personnel and the workload they must bear. The high demands from patients' families and the complexity of handling psychiatric patients make nurses at RSKD Dadi have a high risk of experiencing work stress and mental fatigue. The purpose of this study was to understand the factors that influence the mental health of nurses in the inpatient (psychiatric) room of the Dadi Regional Special Hospital (RSKD) of South Sulawesi Province, Makassar City, in 2025. The research design is a cross-sectional study; this study is a quantitative study with a descriptive approach. Using the Slovin formula, a population of 100 nurses was determined to be 80, with 80 serving as the research sample. This data analysis used a multiple logistic regression. The results of multiple logistic regression tests, there is an influence between work stress on mental health, namely (p = 0.000 <0.05), there is an influence between workload on mental health, namely (p = 0.045 <0.05), there is no influence between the physical work environment on mental health, namely (p = 0.126 ≥ 0.05), there is no influence of interpersonal relationships on mental health (p = 0.939 ≥ 0.05) on nurses in the inpatient (mental) ward of RSKD Dadi Makassar City. RSKD Dadi Makassar City should immediately evaluate the staffing arrangement, especially in the nursing sector, to address the imbalance between the number of nurses and patients. Moreover, it can develop a similar program,